2019
DOI: 10.1016/j.micpath.2019.103762
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic acid (MPA) modulates host cellular autophagy progression in sub genomic dengue virus-2 replicon cells

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Regarding mycophenolate mofetil (MMF) and mycophenolic acid (MPA), MMF is a prodrug of MPA and both of them are immunosuppressants used to prevent rejection of transplant [ 18 ]. MMF and MPA have been reported to have antiviral activity against Hepatitis C Virus (HCV), human herpes virus, DENV, and SARS-CoV-2 [ 19 , 20 , 21 , 22 ]. We found that the addition of gemcitabine, MMF, and MPA could significantly inhibit SADS-CoV infection and replication, especially by inhibiting the post-entry stages ( Figure 4 C–E).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding mycophenolate mofetil (MMF) and mycophenolic acid (MPA), MMF is a prodrug of MPA and both of them are immunosuppressants used to prevent rejection of transplant [ 18 ]. MMF and MPA have been reported to have antiviral activity against Hepatitis C Virus (HCV), human herpes virus, DENV, and SARS-CoV-2 [ 19 , 20 , 21 , 22 ]. We found that the addition of gemcitabine, MMF, and MPA could significantly inhibit SADS-CoV infection and replication, especially by inhibiting the post-entry stages ( Figure 4 C–E).…”
Section: Resultsmentioning
confidence: 99%
“…CSJD may inhibit the occurrence of autophagy by down-regulating the expression of AKT1 by targeting, thus hindering the replication of dengue virus. [ 39 ] STAT3 is a key transcription factor mediating the early response of dengue shock syndrome. Relevant studies have suggested that the decrease of STAT3 level can lead to a significant decrease in the expression and replication of dengue virus protein, and CSJD may inhibit the expression and replication of Dengue virus by reducing the level of STAT3 in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mycophenolic acid is commonly used for the prevention of rejection in kidney and liver transplantation and has been shown to inhibit flavivirus infection in mammalian cells by preventing the synthesis and accumulation of viral RNA, to suppress DENV2 infection in mosquito midguts and dissemination to salivary glands when administered through a blood or sugar meal, and to inhibit ZIKV infection in both mosquito cells and adults [ 41 , 42 ]. In addition, Mycophenolic acid has been documented to have antiviral activity against many viruses ( Table 7 ) [ 17 , 43 , 44 , 45 , 46 , 47 ]. Mycophenolic acid has previously been shown to exhibit anti-ZIKV activity in Vero cells infected with ZIKV SL1602 strain (EC 50 of 0.42 µM); in Huh7, HeLa and HAEC cells infected with ZIKV MEX_I_7 strain (EC 50 < 2 µM); in U2OS cells infected with ZIKV MEX-2-81 strain (EC 50 of 0.4 µM); and in JEG-3 and HBME cells infected with a ZIKV cocktail of MR-766, FSS13025, and MEX-2-81 strains (EC 50 of 0.1 µM) and inhibitory effects were described in Vero cells infected with ZIKV MR-766 (EC 50 of 0.11) and PRVABC59 (EC 50 0.14 µM) [ 24 , 34 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%